PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF MAHASISWA PADA MATA KULIAH KEWIRAUSAHAAN - Rusmin AR; Deskoni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
This research aims to improve the skill of student creative thinking in the entrepreneurship learning through the group investigation in the cooperative learning models. The method used the classroom action research. Data were collected through test of creative thinking skills on the essay form, observations, and questionnaires. The results showed increased the creative thinking skills in the entrepreneurship learningfrom 71,7 up to 86,5. Increased indicators of fluency were 1,9%, flexibilityin first cycle were 5,4%, elaborationin the first cycle were 3,8%, and evaluationin the first cycle were 3,8%. Based on this research, the group investigation in the cooperative learning modelscan be used as one of alternatives models in the entrepreneurship learning by lecturer to improve the skill of student creative thinking especially in the entrepreneurship learning.